Molecular Modeling Basic Principles and Applications - Höltje, Hans-Dieter Sippl, W (Methods and principles in medicinal chemistry, v. 5., 2008)
"Ideal for beginners, this book explains the basics of modeling in a competent yet easily understandable way, with completely worked-out examples to guide readers to their first modeling experiments. This third edition features a new chapter on chemogenomics, reflecting the trend towards 'chemical biology', while the example of protein modeling is completely rewritten for a better 'feel' of modeling complex biomolecules. The authors are experienced university lecturers who regularly hold courses on molecular modeling, making this a tried-and-tested text for teachers. It is equally valuable for experts, since it is the only book to evaluate the strengths and limitations of the molecular modeling techniques and software currently available.